Arthur Guiterman papers - Guiterman, Arthur, 1871-1943.
Typewritten poems signed by Guiterman, limericks, notes, and handwritten drafts of poems. Includes fragments of letters from Guiterman to Eleanor Graham.
Humorist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Graham, Eleanor, -- 1896-1984 -- Correspondence; American wit and humor; Humorous poetry, American; Humorists